Perspectives on Quality and Innovation in Higher Education. A Critical look - Zeledón Ruiz, María del Pilar (2022)
This article presents the critical view of eleven experts in quality management and innovation from prestigious Universities, Colleges and Business Schools in countries such as Spain, Mexico, Colombia and Costa Rica. It is about recognizing from their criteria, the importance of quality and innovation in Higher Education, the lessons learned derived from these experiences, current trends and their prospective vision. To do this, a descriptive study was carried out, under a qualitative approach that supported by the Delphi Method, collects these perceptions through a face-to-face interview, which was carried out in person or with the support of a virtual platform. Given the health measure that was taken, in the last stage of the investigative process, in the face of the situation generated by the COVID 19 pandemic. For the processing and analysis of the information, the ATLAS.ti version 8.4.24.0 tool was used. The results show that the complementarity of innovation and quality is vital for the management and sustainability of Universities, called to be engines of development in any country. This binomial contributes to effectiveness and efficiency, to the generation of bridges and networks of strategic cooperation, to the management of change and the opening of opportunities for the flourishing of humanity.